2020
DOI: 10.1038/s41598-020-72570-x
|View full text |Cite
|
Sign up to set email alerts
|

Human spatial memory implicitly prioritizes high-calorie foods

Abstract: All species face the important adaptive problem of efficiently locating high-quality nutritional resources. We explored whether human spatial cognition is enhanced for high-calorie foods, in a large multisensory experiment that covertly tested the location memory of people who navigated a maze-like food setting. We found that individuals incidentally learned and more accurately recalled locations of high-calorie foods – regardless of explicit hedonic valuations or personal familiarity with foods. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In addition, a large body of evidence indicates that specific foods, such as whole, plant-based foods, have the potential to reduce inflammatory activity ( Ricker and Haas, 2017 ), while accumulating evidence indicates that dietary habits also influence sleep physiology ( St-Onge et al., 2016 ; Frank et al., 2017 ). Finally, limited data from both animal ( Ross et al., 2009 ; Zhao et al., 2017 ; Henry and Stoner, 2011 ; Rendeiro et al., 2013 ) and human studies ( de Vries et al., 2020 ) have suggested that shifts in dietary habits might also impact spatial memory processes.…”
Section: Interventions Targeting Sleep Disturbance and Inflammationmentioning
confidence: 99%
“…In addition, a large body of evidence indicates that specific foods, such as whole, plant-based foods, have the potential to reduce inflammatory activity ( Ricker and Haas, 2017 ), while accumulating evidence indicates that dietary habits also influence sleep physiology ( St-Onge et al., 2016 ; Frank et al., 2017 ). Finally, limited data from both animal ( Ross et al., 2009 ; Zhao et al., 2017 ; Henry and Stoner, 2011 ; Rendeiro et al., 2013 ) and human studies ( de Vries et al., 2020 ) have suggested that shifts in dietary habits might also impact spatial memory processes.…”
Section: Interventions Targeting Sleep Disturbance and Inflammationmentioning
confidence: 99%
“…Olfaction has been described as an inherently emotionally evocative sense and is well integrated with the limbic system (Soudry et al, 2011). Olfaction is involved in detecting and identifying health hazards (e.g., fire, bad food) and food and nutrition (de Vries et al, 2020;Stevenson, 2010). This link between olfaction and survival might explain the emotional nature of the olfactory system.…”
Section: Introductionmentioning
confidence: 99%
“…Put generally, value information is expected to serve as input to any and all systems whose use of value information would have redounded in net fitness benefits ancestrally. There is evidence that food value information, for instance, is used internally to regulate-in addition to social value and social emotions-appetite (Hinton et al, 2004), visual attention (Motoki et al, 2018; see also Krajbich et al, 2010), spatial memory (New et al, 2007;de Vries et al, 2020), foraging decisions (Hill et al, 1987), sharing decisions (Gurven, 2004;Kaplan et al, 1985;Kaplan et al, 2012), disgust and nausea (Profet, 1992), and food taboos (Fessler et al, 2002;Henrich & Henrich, 2010;Navarrete & Fessler, 2003). How and where human value information is computed and routed internallythe human valuome-is yet to be mapped comprehensively.…”
Section: Discussionmentioning
confidence: 99%